A wellness application: use of imagery for athletes` stress reduction and relaxation - Alicea, S.; Sackett, S. C.; Winter, A. (Journal of Imagery Research in Sport and Physical Activity, 2024)
In a world of intense physical and mental demands, high-pressure situations, competing priorities, and sometimesmore failures and setbacks than successes, sport is a contextwhere the term"stress"may feel like an understatement.Fortunately, an acknowledgement that excessive and pro-longed stress not only undermines athletic performance butcan significantly impact the mental health of participants hasbecome a growing concern and focus of research, interven-tion efforts, and dedicated resources across competitive sportlevels [1-7]. While stress management techniques have beenconsidered sound performance enhancement tools for sometime, a more recent trend has considered the utility of thesestrategies for the benefit of the whole athlete, both on and offthefield [8, 9]. While a slew of stress management tech-niques exists, one whose function has been theorized to helpmediate levels of arousal resulting from stressors in sport ismental imagery [10]. Interestingly, though, empirical studyof the efficacy of imagery to reduce stress is limited in someways-e.g., more focused on performance as opposed towellness-enhancement and more commonly targeting cogni-tive appraisals of one`s anxiety as opposed to imparting anarousal-reduction/relaxation response [11]. While there issome justification for avoiding low levels of arousal formany sport task demands, we propose there is a significant need for athletes to have tools for managing maladaptivestress responses for certain sport performances and one thatcould also serve as a viable stress coping mechanism for all.Therefore, the aim of this paper is to review the currentliterature on (a) stress management and relaxation in sportand (b) mental imagery for managing general and sport-specific arousal such as stress reduction to build a case forimagery as a multipurpose and accessible wellness tool.